2009
DOI: 10.1002/ird.535
|View full text |Cite
|
Sign up to set email alerts
|

Predicting water allocations and trading prices to assist water markets

Abstract: Uncertain water allocations and water trading prices are a key constraint to efficient irrigated cropping and water trading decisions. This study shows that neural network models can reasonably forecast seasonal allocations and trading prices in water markets. These models can complement other forecasting techniques such as regression analysis and time series models as the former can better capture the non-linearities in the water trading system. Using a 50% probability risk factor for water variability, the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…If this scenario eventuates, 'Low Security' entitlements may yield significantly less water than models anticipate. This outcome could also affect the ability of irrigators who rely on 'Low Security' entitlements to plan for the coming agricultural season (Khan et al 2010). In his recent report to the Governor of South Australia, Commissioner Bret Walker (2019) recounted two opposing impressions from his experience of conducting the Royal Commission:…”
Section: Resultsmentioning
confidence: 99%
“…If this scenario eventuates, 'Low Security' entitlements may yield significantly less water than models anticipate. This outcome could also affect the ability of irrigators who rely on 'Low Security' entitlements to plan for the coming agricultural season (Khan et al 2010). In his recent report to the Governor of South Australia, Commissioner Bret Walker (2019) recounted two opposing impressions from his experience of conducting the Royal Commission:…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, what has to be taken into consideration is that: ‘economic risk is pervasive in agriculture due to climatic variability and irrigated agriculture is no exception’ (Shahbaz Khan et al ., ); investing in irrigation infrastructures requires such a huge amount of money that they should be maintained as long as possible, so as to prevent the owner—government, public authority, water user association—from having to reinvest for rehabilitation. It is therefore necessary to include long‐term renewal in the initial financial equation; head structures are most of time not delivering an individual service.…”
Section: Some Guidelines For Addressing the Issuementioning
confidence: 99%
“…Water markets are strictly regulated as regards trading zones and price mechanisms. Ideally they should enhance water resource allocation efficiency without impacting on the environment or social equity (Shahbaz Khan et al, 2009). Transactions are facilitated by traders, who are paid by sellers, while buyers pay duties and taxes on the said transaction.…”
Section: Payment For Water Resource Conservation; Water Market Mechanismmentioning
confidence: 99%
“…An adaptive learning model for predicting availability of water for allocation has been developed in this study for Murrumbidgee irrigation area (MIA), New South Wales, Australia that learns from results of detailed hydrological models and ocean‐based climate forecasts using artificial neural network (ANN) technique. Extensions of this model to predict water prices have been made by Khan et al [2009] while earlier versions of this work can be found at Khan et al [2004, 2005].…”
Section: Introductionmentioning
confidence: 99%